OBSERVASI KADAR SGOT DAN SGPT PADA PEROKOK AKTIF BERDASARKAN USIA DEWASA DI WILAYAH BUKUAN RT 13 - Annisa Putri Yasmeen (Akademi Kesehatan John Paul II Pekanbaru, 2023)
Smoking is a common bad habit worldwide and has the potential to cause a variety of serious diseases, including liver disorders. The enzymes SGOT and SGPT are used as sensitive indicators to measure liver function. This study aims to determine the levels of SGOT and SGPT in adult active smokers in the Bukuan RT 13 area. This study used descriptive method and cross sectional research design. The study population consisted of 20 adult active smokers in Bukuan RT 13 with total sampling technique. Data obtained from the results of the examination of SGOT / SGPT levels and interviews then analyzed univariate. The results showed that of the 20 respondents, all (100%) were active smokers with a smoking duration of more than 5 years. Abnormal SGOT levels were found in 12 people (60%), while SGPT was normal in 18 respondents (90%). The group who smoked 11-20 cigarettes per day had 5 respondents (25%) with normal SGOT results, while the group who smoked more than 20 cigarettes per day had 8 respondents (40%) with abnormal SGOT levels. Normal SGPT levels were found in 10 respondents (50%) from the group who smoked more than 20 cigarettes per day. The conclusion of this study is that some respondents showed abnormal SGOT and SGPT levels, which indicates the need for attention in the prevention and management of smoking-related health problems in active smokers with a smoking duration of more than 5 years.